2017
DOI: 10.1001/jamaneurol.2017.0477
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Primary Stroke Center Protocol for Suspected Stroke by Large-Vessel Occlusion With Efficiency of Care and Patient Outcomes

Abstract: IMPORTANCE While prehospital triage to the closest comprehensive stroke center (CSC) may improve the delivery of care for patients with suspected emergent large-vessel occlusion (ELVO), efficient systems of care must also exist for patients with ELVO who first present to a primary stroke center (PSC). OBJECTIVE To describe the association of a PSC protocol focused on 3 key steps (early CSC notification based on clinical severity, vessel imaging at the PSC, and cloud-based image sharing) with the efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 28 publications
4
64
0
Order By: Relevance
“…Studies have demonstrated a robust benefit of mechanical thrombectomy (MT) in patients presenting with acute ischemic stroke (AIS) due to proximal anterior circulation large vessel occlusion (LVO) leading to efforts tailored to improve triaging AIS patients in the field and upon arrival to the emergency department (ED) . Thus, to facilitate appropriate triage and prompt ED diagnosis and treatment of LVO, it is important to develop assessment tools that can reliably predict LVO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated a robust benefit of mechanical thrombectomy (MT) in patients presenting with acute ischemic stroke (AIS) due to proximal anterior circulation large vessel occlusion (LVO) leading to efforts tailored to improve triaging AIS patients in the field and upon arrival to the emergency department (ED) . Thus, to facilitate appropriate triage and prompt ED diagnosis and treatment of LVO, it is important to develop assessment tools that can reliably predict LVO.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of data from the Field Administration of Stroke Therapy trial – Magnesium (FAST‐MAG) comparing eight scales for LVO recognition suggested that the Los Angeles Motor Scale (LAMS) was comparable or superior to other scales used in the prehospital or ED setting, in its ability to predict LVO . There is evidence that suggests that an LAMS ≥ 4 is a good predictor of LVO and this threshold is oftentimes used in triage and decision‐making . Additionally, a recent study showed that atrial fibrillation (AF) correlates with the presence of LVO .…”
Section: Introductionmentioning
confidence: 99%
“…Efficient evaluation and administration of alteplase make initial NECC triage a viable strategy, even when in close proximity to an ECC. In practice, however, DTN times under 30 min appear difficult to achieve, even with optimized protocols in place 10. Despite process improvements, recent reports show that even DTN times under 60 min are often unfeasible, and continue to comprise the minority of cases 11 12…”
Section: Best Available Evidencementioning
confidence: 99%
“…To prevent such delays, it is essential that thrombectomy centers work closely with their referral hospitals to develop protocols leveraging the early identification of thrombectomy eligible LVO patients now possible though advanced imaging. Even with CTA alone, it has been shown that a strategy consisting of timely CTA performance at nonthrombectomy sites, early communication to the referral thrombectomy center, and efficient electronic image sharing between hospitals can improve efficiency and outcomes …”
mentioning
confidence: 99%